Linguistic Landscape in Sidoarjo City (Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
Linguistic landscape research has been administered in different parts of the world by several researchers. However, linguistic landscape research in Indonesia is still limited in number. To respond to the scarcity of linguistic landscape study in Indonesia, the present research discusses the visible languages, proportions of top-down and bottom-up signs in Sidoarjo City. The functions of the signs are also identified.Data were collected from signs in some public places and along the main streets of Sidoarjo City.The results of the study show that the linguistic landscape is dominated by Indonesian. English is used more often than Arabic. Javanese as the mother tongue for the majority of the society of Sidoarjo is rarely used. Some other Asian languages are also apparent in the shopping centers. Description and explanation of the functions of the signs are also presented.